Improved survival for HIV infected patients with severe Pneumocystis jirovecii pneumonia is independent of highly active antiretroviral therapy. Issue 8 (6th April 2006) - Miller, R F; Allen, E; Copas, A; Singer, M; Edwards, S G
Abstract : Background: Despite a decline in incidence of Pneumocystis jirovecii pneumonia (PCP), severe PCP continues to be a common cause of admission to the intensive care unit (ICU) where mortality remains high. A study was undertaken to examine the outcome from intensive care for patients with PCP and to identify prognostic factors. Methods: A retrospective cohort study was conducted of HIV infected adults admitted to a university affiliated hospital ICU between November 1990 and October 2005. Case note review collected information on demographic variables, use of prophylaxis and highly active antiretroviral therapy (HAART), and hospital course. The main outcome was 1 month mortality, either on the ICU or in hospital. Results: Fifty nine patients were admitted to the ICU on 60 occasions. Thirty four patients (57%) required mechanical ventilation. Overall mortality was 53%. No patient received HAART before or during ICU admission. Multivariate analysis showed that the factors associated with mortality were the year of diagnosis (before mid 1996 (mortality 71%) compared with later (mortality 34%; p = 0.008)), age (p = 0.016), and the need for mechanical ventilation and/or development of pneumothorax (p = 0.031). Mortality was not associated with sex, ethnicity, prior receipt of sulpha prophylaxis, haemoglobin, serum albumin, CD4 count, Pao 2, A-ao 2 gradient, co-pathology in bronchoscopic lavage fluid, medical co-morbidity, APACHE II score, or duration of mechanical ventilation. Conclusions: Observed improved outcomes from severe PCP for patients admitted to the ICU occurred in the absence of intervention with HAART and probably reflect general improvements in ICU management of respiratory failure and ARDS rather than improvements in the management of PCP.